Awareness of cancer, satisfaction with care, emotional distress, and adjustment to illness: an Italian multicenter study. Issue 9 (23rd February 2015) - Costantini, Anna; Grassi, Luigi; Picardi, Angelo; Brunetti, Serena; Caruso, Rosangela; Nanni, Maria Giulia; Bonetti, Luisa; de Feudis, Rossana; Barni, Sandro; Marchetti, Paolo
Abstract Objective The aim of the study was to examine awareness of cancer and the relationship with distress and satisfaction with care among Italian cancer patients. Methods Two hundred sixty‐two cancer patients consecutively admitted to the Day Hospital of four cancer centers in Italy completed the European Organisation for Research and Treatment of Cancer (EORTC) Quality of Life Questionnaire Core‐30, the EORTC Inpatient Satisfaction‐32, the EORTC Information Questionnaire‐25, the distress thermometer, the Mini‐mental Adjustment to Cancer scale, a visual analogue scale of illness awareness, and questions related to the admission and unmet needs. Results Eighty‐seven percent of patients were aware of their diagnosis, but 49% of those with metastatic cancer thought they have a curable disease. About one‐third felt that family members often (16%) or always (13%) were hiding information or bad news in order to protect them. In multivariate analysis, the perception of being protected from bad news by the family was associated with the perceived need to talk more with the family but was not associated with demographic or clinical (Karnofsky Performance Status and stage) variables, lower emotional distress, and greater satisfaction with care and information. Also, awareness of diagnosis and prognosis was not associated with demographic or clinical variables, emotional distress, or satisfaction with care and information Conclusions Most cancer patients were fully informed about their diagnosis, although awareness of disease was not coincident with awareness of prognosis and disease progression. Information and knowledge were not destructive of hope and did not increase distress. Family issues are still a significant factor molding openness and sharing of information. Copyright © 2015 John Wiley & Sons, Ltd.